2005
DOI: 10.1021/jf051365b
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of Inorganic Arsenic in Cooked Rice:  Practical Aspects for Human Health Risk Assessments

Abstract: Arsenic is present in rice grain mainly as inorganic arsenic. Little is known about the effect of cooking on inorganic arsenic content in rice and its bioavailability. This study evaluated total arsenic and inorganic arsenic in rice cooked with arsenic-contaminated water, the bioaccessibility of As(III) and As(V) after simulated gastrointestinal digestion, and the extent of arsenic retention and transport by Caco-2 cells used as a model of intestinal epithelia. After cooking, inorganic arsenic contents increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
132
2
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(151 citation statements)
references
References 19 publications
14
132
2
3
Order By: Relevance
“…For all of the rice products for speciation, the predominant As species are inorganic (75.2-90.1%), with the remainder being DMA. Inorganic As and DMA are known to be the main As components of both white and brown rice (Laparra et al, 2005;Meharg et al, 2008a,b,c;Smith et al, 2006;Williams et al, 2005Williams et al, , 2006Williams et al, , 2007a, while Meharg et al (2008c) has shown that inorganic arsenic is elevated in the bran layer of rice, resulting in brown rice having a higher inorganic content than corresponding white rice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For all of the rice products for speciation, the predominant As species are inorganic (75.2-90.1%), with the remainder being DMA. Inorganic As and DMA are known to be the main As components of both white and brown rice (Laparra et al, 2005;Meharg et al, 2008a,b,c;Smith et al, 2006;Williams et al, 2005Williams et al, , 2006Williams et al, , 2007a, while Meharg et al (2008c) has shown that inorganic arsenic is elevated in the bran layer of rice, resulting in brown rice having a higher inorganic content than corresponding white rice.…”
Section: Resultsmentioning
confidence: 99%
“…For food, the level of 1 mg/kg total As is often cited with respect to rice (The Stationary Office, 1959), which equates to the 1959 UK standard (The Stationary Office, 1959). If As in rice is bioavailable, which all evidence points towards (Laparra et al, 2005;Smith et al, 2006), the toxicity of arsenic mobilized across the gut wall will be the same whether it is derived from water or food. On an equivalence basis, 100 g of 0.1 mg/kg inorganic As in food equates to 1 l of 0.01 mg/l water, remembering that water limits are set in the US and EU based on the assumption that 1 l of water is consumed per day.…”
Section: Resultsmentioning
confidence: 99%
“…Bioavailability of iAs has been shown to be high (63-99%) (Juhasz et al, 2006;Laparra et al, 2005). In this study we assumed a 100% bioavailability for iAs, as it has been assumed by others (Adomako et al, 2011;Batista et al, 2011;Jorhem et al, 2008;Meharg et al, 2009;Meliker et al, 2006;Mondal and Polya, 2008;Qian et al, 2010;Torres-Escribano et al, 2008;Tsuji et al, 2007;Ye et al, 2012).…”
Section: Limitations and Research Needsmentioning
confidence: 95%
“…Method of cooking the rice and As content of water used in cooking may also play a significant role. Increasing water As concentration has been shown to increase the As level in the cooked rice; cooking with aliquots of water (steaming) or until dryness do not affect the As level in cooked rice, while cooking with abundant water and discarding the excess water has been shown to decrease As level compared to raw rice (Fontcuberta et al, 2011;Laparra et al, 2005;Mihucz et al, 2010Mihucz et al, , 2007Raab et al, 2009;Rahman et al, 2006;Sengupta et al, 2006;Torres-Escribano et al, 2008). Rinsing with water prior to cooking also reduces the As content (Mihucz et al, 2007;Raab et al, 2009;Sengupta et al, 2006) because rice contains considerable portion of tAs in its bran and outer grain than its bulk (Sun et al, 2008).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Cooking and washing foods in iAs-contaminated water have also been shown to increase the iAs concentration in the prepared food [147], especially in rice [25,148,149]. However, cooking of rice in water which has not been contaminated with iAs, rinse washing before cooking and cooking with large volume of water seem to decrease the iAs content in the prepared food [147,150,151].…”
Section: Effect Of Storage and Processing On Concentration And Stabilmentioning
confidence: 99%